Locating Forced Migrants’ Resources: Residency Status and the Process of Family Reunification in Finland - Johanna Hiitola (Social Inclusion, 2019)
This article investigates how forced migrants residing in Finland utilise different types of resources in their efforts to reunite with their families. The data includes 36 group and individual interviews (2018–2019) with 43 Iraqi, Afghan, Somali, and Ethiopian forced migrants holding residence permits in Finland, who were either seeking to reunite with their families, or had already brought their families to Finland, or had attempted but failed to achieve family reunification. The results show that a variety of resources are needed to navigate the bureaucracies involved in family reunification. Economic resources in one’s country of origin may be used to pay the high administrative and travel costs, as well as other fees required by government officials to obtain visas for family members. Cultural resources, such as education, are useful when one is trying to make sense of the complicated application process, or seeking work or educational opportunities in the new country. Different forms of social resources can be utilised to seek advice. However, the resources at the disposal of migrants are not the determining factor in attempts to successfully reunite with one’s family. Although they are important, the success of the reunification process depends more on one’s residency status and whether it allows family reunification without a high-income requirement.